Peran Badan Perencanaan Pembangunan Riset dan Inovasi Daerah dalam Meningkatkan Pendapatan Asli Daerah Melalui Pemungutan Pajak Daerah di Kabupaten Sikka - Frumensia Katensia; Yosefina Andia Dekrita; Imanuel Wellem (Dharma Ekonomi, 2024)
This study aims to find out the role of the Regional Research and Innovation Development Planning Agency in increasing the original regional income of Sikka Regency through collecting regional taxes in Sikka Regency. The problems faced during the last 2 years in the Regional Tax sector, namely targets and realizations from 2022 and 2023, are not significant. This is caused by several things, namely the lack of maximum attention from the planning side to increasing Original Regional Income from the tax sector, decreased awareness of taxpayers, decreased public awareness, lack of coordination, data base that has not been updated. The research method used is a qualitative method. Data collected through interviews and analyzed qualitatively. The results of this research show that BAPPERIDA has three main roles in increasing Original Regional Income through Regional Tax Collection, namely Planning, Coordinating and Evaluation Monitoring.